The role of reduced intracellular concentrations of active drugs in the lack of response to anticancer chemotherapy - Marin Jose JG; Monte Maria J; Blazquez Alba G; Macias Rocio IR; Serrano Maria A; Briz Oscar (Acta Pharmacologica Sinica; Vol 35, No 1 (January 2014): Acta Pharmacologica Sinica, 2016)
Jose JG MARIN*, Maria J MONTE, Alba G BLAZQUEZ, Rocio IR MACIAS, Maria A SERRANO, Oscar BRIZ Laboratory of Experimental Hepatology and Drug Targeting (HEVEFARM), Biomedical Research Institute of Salamanca (IBSAL), University of Salamanca, National Institute for the Study of Liver and Gastrointestinal Diseases (CIBERehd), Spain A major difficulty in the treatment of cancers is the poor response of many tumors to pharmacological regimens. This situation can be accounted for by the existence of a variety of complex mechanisms of chemoresistance (MOCs), leading to reduced intracellular concentrations of active agents, changes in the molecular targets of the drugs, enhanced repair of drug-induced modifications in macromolecules, stimulation of anti-apoptotic mechanisms, and inhibition of pro-apoptotic mechanisms. The present review focuses on alterations in the expression and appearance of the genetic variants that affect the genes involved in reducing the amount of active agents inside tumor cells. These alterations can occur through two mechanisms: either by lowering uptake or enhancing efflux (so-called MOC-1a and MOC-1b, respectively), or by decreasing the activation of prodrugs or enhancing inactivation of active agents through their biotransformation (MOC-2). The development of chemosensitizers that are useful in implementing the pharmacological manipulation of these processes constitutes a challenge to modern pharmacology. Nevertheless, the important physiological roles of the most relevant genes involved in MOC-1a, MOC-1b, and MOC-2 make it difficult to prevent the side effects of chemosensitizers. A more attainable goal in this area of pharmacological enquiry is the identification of proteomic profiles that will permit oncologists to accurately predict a lack of response to a given regimen, which would be useful for adapting treatment to the personal situation of each patient. Keywords: cancer; anticancer drug; chemoresistance; ATP-binding cassette protein; drug refractoriness; drug metabolism; cytochrome P450-related enzyme; prodrug; plasma membrane transporter The revision of the English spelling, grammar, and style of the manuscript by N Skinner is gratefully acknowledged. * To whom correspondence should be addressed. E-mail jjgmarin@usal.es Received 2013-07-02 Accepted2013-08-23